SWOT ANALYSIS OF VILLAGE ROAD INFRASTRUCTURE PLANNING CASE STUDY OF TRAFFIC CONGESTION IN MEDAN JOHOR REGENCY - Feby Milanie; Ruri Prihatini Lubis; Ria Pratiwi Atmaja; Hasqiban Ritonga; Wahyu Rinaldi; Azura Cahaya Purnomo (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to analyze development planning issues and their impact on traffic congestion on Jalan Luku and Jalan Pintu Air, Kwala Bekala Village, Medan Johor District. Kwala Bekala Village is the second largest area with the highest population density, experiencing significant traffic congestion because it functions as a connecting route for settlements and the main access to tourist attractions (the Zoo). The main problems are spatial inconsistencies such as the conversion of road shoulders into illegal parking and street vendors (PKL), unplanned and overlapping infrastructure planning, and weak institutional controls that lead to violations of regional spatial planning. Traffic density causes congestion that disrupts time efficiency and road users. This study uses a qualitative descriptive approach with a case study method. Data were obtained through direct observation of traffic flow movements at certain hours at the study location. Data were analyzed using SWOT to identify strengths, weaknesses, opportunities, and threats that can formulate strategies for handling congestion. The SWOT analysis results indicate that the main weaknesses lie in road narrowing and misuse of road shoulders, while the greatest threats are the growth rate of private vehicles, which is faster than infrastructure development, and weak law enforcement. This study identifies four main strategies that must be implemented to sustainably increase traffic capacity and smoothness: (1) Accelerating improvements in road capacity and conditions, (2) Developing comfortable and integrated mass transportation, (3) Enforcing regulation of road shoulder misuse.